Konflik Peran Ganda Perempuan Pengusaha Industri Kecil di Kabupaten Bangkalan Madura - Nurita Andriani; - Faidal (Trunojoyo University of Madura, 2008)
The critical problem that faced by women entrepreneur was the strain / conflict which appear between way of life and career, the strain was reflected by conflict role. That’s were business and household. That was the problem that faced by women entrepreneur of batik small business in Bangkalan Madura. This research was aimed to know the factors that influencde business-related factors, family-related factors, personal factor to the double role conflict of small business in Bangkalan. Batik small business was used as a research object, because over 50% batik handycraf was women. This research placed at Tanjung Bumi which use 54 respondens as the sample, which were taken from three villages, desa Tanjung, desa Telaga Biru, and desa Paseseh. The result of this research showed that comfortability of life, self-respect, business satisfaction, time of work, children dan the liquidity of the business had significant influence to the double role conflict of the women entrepreneur in batik small business. Filling comfortable because she could help to increase the welfare of the family by having a business, were the domain factor which could eliminate the double role conflict to the women entrepreneur. Married happiness, worker and education had no significant influence to the double role conflict of the women entrepreneur.